Variation in Preferred Leadership Styles Across Generations - Andy Bertsch; Mohammad Saeed; James Ondracek; ABM Abdullah; Josh Pizzo; Jordan Dahl; Shain Scheschuk; Wyatt Moore; Danny Youngren (Journal of Leadership in Organizations, 2022)
Introduction/Main Objectives: This study investigated preferred leadership styles across Baby Boomers, Generation X, and Millennials. The autocratic, participative, and laissez-faire were identified as the most prevalent styles; and were assessed to explore how the leadership styles across generations affect the role of leadership. Background Problems: Although leadership styles and perspectives have been investigated from divergent angles, the preferred leadership styles have not been explored adequately across generations. Novelty: This study endeavored at filling the gap in the literature, and to provide direction to stakeholders, as regards the preference of each generation for a particular leadership style. Research Methods: An exploratory research design was used for this study and questionnaire items were adopted from the Globe Leadership and Organizational Behavior Effectiveness (GLOBE) project. The sample was obtained from adults over the age of eighteen from the Midwest USA and Canada.  Finding/Results: The study confirmed the generally- accepted hypothesis that Baby Boomers tend to be workaholics and career-driven. The study provides direction and motivation for further confirmatory and exploratory studies pertaining to preferred leadership styles vis-à-vis generation as well as demographic, geographic, and cross-cultural variables. Conclusion: Generation X is highly focused on family, life, and work. The millennial generation has modern values and believes in treating everyone equally, though with a desire to be the center of attention for stealing the spotlight.